When a U.S. president demanded inspections of a nuclear facility in the Middle East (and failed) (Mondoweiss, 2015)
Four months before he died, President John Kennedy told Israel’s PM that American support of Israel ‘could be seriously jeopardized’ if Israel did not let the United States obtain…